The Effectiveness Of E-Learning At Perak Entrepreneur And Skills Development Centre (PESDC) - Balaraman, Pirema@Prema (2006)
This study is to evaluate the effectiveness of e-learning at PESDC. The focus of this study is to find how PESDC students benefited from e-learning classes, the acceptance level of e-learning and the performance of those who have used the PESDC e-learning system.